Anmeldelse af The Return of Inequality: Social Change and the Weight of the Past - Arabi, Kasper (Politica, 2022)
Mike Savage, The Return of Inequality: Social Change and the Weight of the Past. Harvard University Press, 2021 (anmeldt af Kasper Arabi)